2014
DOI: 10.1128/jvi.02068-13
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 4α and Downstream Secreted Phospholipase A 2 GXIIB Regulate Production of Infectious Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) is a major cause of chronic hepatitis, liver cirrhosis, and hepatocellular carcinoma in humans. The life cycle of HCV is closely associated with the metabolism of lipids, especially very-low-density lipoprotein (VLDL) in hepatocytes. Hepatocyte nuclear factor 4␣ (HNF4␣), the most abundant transcription factor in the liver, regulates the VLDL secretory pathway. However, the effects of HNF4␣ on the HCV life cycle are unclear. In this study, we investigated the regulatory effects of HNF4␣ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
(69 reference statements)
1
40
0
Order By: Relevance
“…4B). Next, shRNA-transduced cells were infected with HCV JFH1 at a low MOI of 0.02, ensuring multiple cycles of infection, which could have a comprehensive effect on the viral life cycle (41)(42)(43). At 72 hpi, we found that silencing of vinexin ␤ (2 sh Vin␤ and 3 sh Vin␤) reduced the intracellular HCV RNA level to 44.7 and 32.7% of that in control (sh NT) cells, respectively (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…4B). Next, shRNA-transduced cells were infected with HCV JFH1 at a low MOI of 0.02, ensuring multiple cycles of infection, which could have a comprehensive effect on the viral life cycle (41)(42)(43). At 72 hpi, we found that silencing of vinexin ␤ (2 sh Vin␤ and 3 sh Vin␤) reduced the intracellular HCV RNA level to 44.7 and 32.7% of that in control (sh NT) cells, respectively (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…To further investigate whether CIDEB is involved in the late stage of the HCV life cycle, we calculated the specific infectivity (infectious titer divided by the HCV RNA copy number) and the ratio of the extracellular HCV titer to the intracellular HCV titer, as previously described 18,26 . The specific infectivity was calculated to evaluate the efficiency of HCV assembly 36 , whereas the ratio of the extracellular titer to the intracellular titer was used to evaluate the level of viral particle secretion 18,26 .…”
Section: Resultsmentioning
confidence: 99%
“…The specific infectivity was calculated to evaluate the efficiency of HCV assembly 36 , whereas the ratio of the extracellular titer to the intracellular titer was used to evaluate the level of viral particle secretion 18,26 . Results showed that similar to siApoE, siCiDeB significantly reduced extracellular HCV specific infectivity whereas siCD81 had no effect (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations